Recovery of left ventricular and left atrial mechanics in various entities of aortic stenosis 12 months after TAVI. (12th September 2013) - Spethmann, Sebastian; Baldenhofer, Gerd; Dreger, Henryk; Stüer, Katharina; Sanad, Wasiem; Saghabalyan, Davit; Müller, Eda; Stangl, Verena; Baumann, Gert; Stangl, Karl; Laule, Michael; Knebel, Fabian
Abstract: Background: Transcatheter aortic valve implantation (TAVI) has been shown to improve prognosis of high-risk patients. Data, however, concerning the impact of TAVI on regional and global left atrial (LA) and left ventricular (LV) mechanics in varying entities of severe aortic stenosis (AS) are sparse, particularly in patients with paradoxical low-flow (PLF) AS or with reduced LV ejection fraction (LVEF). This study evaluated the effects of TAVI on LA and LV mechanics in varying entities of AS 12 months after implantation. Methods and results: A total of 54 consecutive patients with severe AS (24 with a normal LVEF and normal flow, 16 with PLF, and 14 with a reduced LVEF) were included. Speckle tracking echocardiography was performed before and 12 months after TAVI to determine LV global and regional longitudinal deformation as well as LA function (reservoir function, conduit phase, and active contraction). In all the three entities of AS, there was a significant improvement in global and regional LV longitudinal function (average global longitudinal strain: −14.1 ± 3.9% at baseline vs. −16.5 ± 4.0% after TAVI, P < 0.001). Interestingly, the beneficial effects were most pronounced in patients with PLF (−14.0 ± 2.9 vs. −17.0 ± 4.4%, P < 0.031). Moreover, the atrial reservoir and conduit function recovered significantly after TAVI in all patients. Conclusion: In conclusion, regardless of the underlying AS entity, TAVI improves global and regional LV and LA mechanics within 12 months.